Revision of the genus Polyeunoa McIntosh, 1885 (Polychaeta, Polynoidae) - Barnich, Ruth; Gambi, Maria Cristina; Fiege, Dieter (Zootaxa, 2012)
Long-bodied polynoids, like Polyeunoa laevis McIntosh, 1885 and similar species which are often associated with cold-water corals, are regularly reported from Antarctic, Subantarctic and adjacent cold-temperate waters. The taxonomy ofthese species is confused and has been subject to various discussions in the past. For the revision presented here weexamined the available type material and additional specimens of the following species: Polynoe antarctica Kinberg,1858, Polyeunoa laevis McIntosh, 1885, Enipo rhombigera Ehlers, 1908, Hololepidella flynni Benham, 1921, Polyeunoedubia Hartmann-Schröder, 1965, Polyeunoa monroi Averincev, 1978, and Polynoe thouarellicola Hartmann-Schröder,1989. As a result we consider Polyeunoa laevis McIntosh, 1885, Parapolyeunoa flynni (Benham, 1921) n. comb., andNeopolynoe antarctica (Kinberg, 1858) n. comb. as valid species. Enipo rhombigera Ehlers, 1908, Polyeunoe dubiaHartmann-Schröder, 1965, and Polynoe thouarellicola Hartmann-Schröder, 1989 are junior synonyms of Polyeunoalaevis. Polyeunoa monroi Averincev, 1978 is a junior synonym of Hololepidella flynni Benham, 1921 for which the newgenus Parapolyeunoa n. gen. is erected. Polynoe antarctica Kinberg, 1858 is transferred to the genus NeopolynoeLoshamn, 1981 and represents the third known species within this genus. Three comprehensive tables illustrating the distinctive characters of the considered genera and species are given to facilitate the identification of the valid species.Keywordstaxonomy, Polyeunoa, Parapolyeunoa n. gen., Neopolynoe, Southern Ocean, SOAP workshop, cold-water corals